Pengaruh Kebijakan Dividen dan Kinerja Keuangan terhadap Tax Avoidance dengan Financial Distress sebagai Variabel Moderasi - Ezra Ragillya Aji; Adi Supriadi (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This study aims to analyze the effect of Dividend Policy and Financial Performance on Tax Avoidance with Financial Distress as a moderating variable. This research was conducted on LQ45 companies listed on the Indonesia Stock Exchange (IDX) during the period 2019 to 2023. The sampling method used in this study was purposive sampling with a total of 17 companies selected as the research sample. The data used in this study is secondary data in the form of financial statements from each sampled company. The independent variables used in this study are Dividend Policy (X1) as the first independent variable, Financial Performance (X2) as the second independent variable, Tax Avoidance (Y) as the dependent variable, and Financial Distress (Z) as the moderating variable. Panel data regression method was used as the research methodology in this study. The analysis of research results was conducted with the assistance of EViews 12 Student Version Lite software. The results showed that the best model is the Common Effect Model (CEM). The findings indicate that simultaneously, Dividend Policy and Financial Performance have a significant effect on Tax Avoidance. Partially, Dividend Policy has a significant effect on Tax Avoidance, and Financial Performance also has a significant effect on Tax Avoidance. Financial Distress is proven to moderate the relationship between Dividend Policy and Tax Avoidance. However, Financial Distress is not proven to moderate the relationship between Financial Performance and Tax Avoidance.